Best practices for clinical trials of deep brain stimulation for neuropsychiatric indications - Tremblay-McGaw, Alexandra G.; Hamlat, Elissa J.; Becker, Natalie C.; Astudillo Maya, Daniela A.; Krystal, Andrew D.; Sellers, Kristin K. (Frontiers in Human Neuroscience, 2025)
Deep brain stimulation (DBS) is well suited to target disorders with network dysregulation, as is the case in many neuropsychiatric diseases. While DBS is a well-established therapy for Parkinson’s disease, essential tremor, dystonia, and medically refractory epilepsy, it is actively being studied in clinical trials for neuropsychiatric disorders including treatment-refractory major depressive disorder (MDD). Due to the nature of symptomology and participant characteristics, special care must be taken in the design and implementation of clinical trials testing DBS for neuropsychiatric disorders. In particular, these studies typically include multi-year relationships between participants and study staff with frequent interactions, high burden of study activities on participants, and disclosure by participants of sensitive information related to symptoms and disease state. Through our experience with six participants across more than 5 years of the Presidio clinical trial assessing personalized closed-loop DBS for treatment-refractory MDD, we have gathered experience and evidence to inform best practices for conducting these interaction-intensive clinical studies in a vulnerable population. Here, we present these Key Practices along with discussion, informed by multiple fundamental principles: The Belmont Report; emotional and physical safety for study participants and staff; and integrity and validity of scientific outcomes.